Analisis Pencapaian Audit Mutu Internal STIKes Mitra Keluarga Rentang 2020-2021 - Anung Ahadi Pradana; Intan Kurnia Putri; Lina Herida Pinem; Susi Hartati; Guntari Prasetya; Elfira Maya Sari; Muhammad Chaidar (UHN IGB Sugriwa Denpasar, 2023)
The Internal Quality Assurance System was one of the ways that can be taken by higher education institutions in maintaining the quality of service and graduates produced as tridharma's responsibility to stakeholders. The purpose of this writing was as STIKes Mitra Keluarga’s responsibility in maintaining a Good University Governance. The method that had been used was a quantitative analysis of data from the implementation of the Internal Quality Audit (AMI) conducted by LPMI STIKes Mitra Keluarga in 2019/20 and 2020/21. The percentage of suitability of the education standards in the 5 study programs at STIKes Mitra Keluarga shows some changes compared to the previous year. Furthermore, the results of the analysis using SPSS on the suitability of education, research, community service, and internal driven standards show a p value > 0.005 which indicates that there was no significant change based on the results of the 2020/2021 AMI with the 2019/2020 AMI results. There had been a decrease in the percentage of suitability in 2020/2021 because even though the number of question items has decreased from the previous year, the content of each question item had been increased in the quality of the standards’ content. Less significant results in 2020/2021 were one of the reasons STIKes Mitra Keluarga had made several changes such as increasing the number of internal driven standards and various questions in each standard as one of the efforts to maintain the quality of STIKes Mitra Keluarga's tridharma.